KEABSAHAN PERJANJIAN JUAL BELI BUBUK KRATOM DI E-COMMERCE MENURUT PASAL 1320 KITAB UNDANG-UNDANG HUKUM PERDATA - Stephanus Christian Situmorang; Nomensen Freddy Siahaan; Dewi Atriani (Universitas Labuhanbatu, 2025)
Online commerce has significantly expanded the circulation of various commodities, including kratom, whose legal status in Indonesia remains controversial. At present, kratom is regulated solely for export purposes and lacks a clear legal basis for domestic trade, creating legal uncertainty in online sale transactions. This study examines the validity of kratom powder sale agreements conducted through e-commerce platforms under Article 1320 of the Indonesian Civil Code and analyzes the legal responsibility of platform providers for facilitating such transactions. The research employs a doctrinal legal method using statutory and conceptual approaches, complemented by an empirical review of kratom listings on major Indonesian e-commerce platforms. The findings indicate that online kratom transactions potentially fail to satisfy the objective requirements of a valid contract, particularly regarding lawful object and lawful cause, due to the absence of explicit domestic regulatory authorization. Empirical observations further reveal inadequate age-verification mechanisms, raising concerns over transactions involving legally incapacitated consumers. This study underscores the urgent need for comprehensive national regulation on kratom and strengthened legal obligations for e-commerce platforms to ensure consumer protection and contractual legality in digital markets.Keywords: contract; validity; kratom; e-commerce platforms; platform liability